Referral in the General Practice in the centre of Portugal: electronic data from two groups of Health Centres - Botas, Philippe (2014)
Introduction: Referral is one of the core competencies of General Practitioners. In 1992, the European study of referrals from Primary to Secondary care indicated a referral rate (RR) of 5.56% in Portugal. In 2003, the RR related to a Health Centre (HC) in the north of Portugal was 10.11 %. At 2012’s WONCA Europe, the authors presented a research introducing a standardized population indicator, Adjusted Referral Calculation (ARC), to study referral in a HC. Objective: Following on from previous research, investigators intended to characterize the informatics generated data of referral, in two groups of Health Centres (GHC) in the centre of Portugal, between 2009 and 2011. Methods: Cross-sectional study. Referral data registered in the computerized system SAM estatística. For each HC, we calculated the RR, (n referral/n total consultations)*100, and the ARC, (n referral*1000/population at the middle of the year*365), that characterizes the number of referral by day adjusted to population at the middle of each year. We analyzed statistical differences in RR and ARC between the two GHC using the Student t test for independent samples. Results: Considering each HC, the RR ranged between 1.48%-5.8% and the ARC between 0.16‰-0.75‰. The lowest and highest values occurred in two HC from the same GHC. The values of RR average ranged between 3.5%-3.79% and 4.74%-5.04%, and the values of ARC average ranged between 0.44‰-0.48‰ and 0.46‰-0.47‰, of the two GHC, respectively. There was no significant difference comparing the RR and ARC averages between the two GHC, except the RR in 2011 (p=0,026). Discussion: The results of RR average for each GHC are lower than what was estimated to Portugal in the European study from 1992. The methodology didn’t consider referral data which wasn’t registered in the program used. However, the authors believe that almost all referrals are made trough the path we studied here. In this research, we found that the lowest and highest values of RR and ARC were recorded in two HC geographically near to each other. This finding promotes reflection about factors that influence the process of referral. ARC allows a more complete analysis between different contexts and complements the information from RR.